World class : - Kanter, Rosabeth Moss (Simon & Schuster, 1995)
The frontier of business growth is shifting from the giants to small and medium-sized enterprises. This book shows how these new pioneers can collaborate, innovate and export. It shows why emerging companies in new technology fields have to be "born global" just to keep their domestic business, why it is so important to act quickly, and how many apparent problems (such as outside ownership of local companies) can be turned to advantage. The book also looks at the development of local communities - cities, boroughs and towns everywhere are developing their own strategic plans and foreign policies - and shows the three ways communities can succeed, explaining how to apply the lessons outlined.